Interfacial Reaction Dependent Performance of Hollow Carbon Nanosphere – Sulfur Composite as a Cathode for Li-S Battery - Zheng, Jianming; Yan, Pengfei; Gu, Meng; Wagner, Michael J.; Hays, Kevin A.; Chen, Junzheng; Li, Xiaohong; Wang, Chongmin; Zhang, Ji-Guang; Liu, Jun; Xiao, Jie (Frontiers in Energy Research, 2015)
Lithium-sulfur (Li-S) battery is a promising energy storage system due to its high energy density, cost effectiveness and environmental friendliness of sulfur. However, there are still a number of technical challenges, such as low Coulombic efficiency and poor long-term cycle life, impeding the commercialization of Li-S battery. The electrochemical performance of Li-S battery is closely related with the interfacial reactions occurring between hosting substrate and active sulfur species which are poorly conducting at fully oxidized and reduced states. Here, we correlate the relationship between the performance and interfacial reactions in the Li-S battery system, using a hollow carbon nanosphere (HCNS) with highly graphitic character as hosting substrate for sulfur. With an appropriate amount of sulfur loading, HCNS/S composite exhibits excellent electrochemical performance because of the fast interfacial reactions between HCNS and the polysulfides. However, further increase of sulfur loading leads to increased formation of highly resistive insoluble reaction products (Li2S2/Li2S) which limits the reversibility of the interfacial reactions and results in poor electrochemical performances. These findings demonstrate the importance of the interfacial reaction reversibility in the whole electrode system on achieving high capacity and long cycle life of sulfur cathode for Li-S batteries.